Cytotoxicity Assessment of Heritiera Littoralis (Aiton), Madhuca Longifolia (König) Macbr., Nerium Indicum Mill. And Sapium Indicum (Willd.) Leaves on Artemia Salina (L.) - Fatema, N; Hasan, K; Islam, A; Yasmin, N; Nesa, M; Islam, N (Journal of Bio-Science, 2021)
Petroleum ether, CHCl3 and CH3OH extracts of leaves of Heritiera littoralis (Aiton), Madhuca longifolia (König) Macbr., Nerium indicum Mill. and Sapium indicum (Willd.) were subjected to assess cytotoxicity against Artemia salina (L.) nauplii. The petroleum ether extract of H. littoralis leaves showed LC50 values 273.77, 97.27, 51.60, 37.12, 14.60 and 12.59 ppm after 12, 18, 24, 30, 36 and 42 h; the CHCl3 extract showed LC50 values 733.25, 105.51, 40.72 and 18.20 ppm after 6, 12, 18 and 24 h whereas CH3OH extract showed 73.05, 30.62, 24.56, 20.85, 16.21 and 6.71 ppm after 6, 12, 18, 24, 30 and 36 h of exposure respectively. The petroleum ether extract of M. longifolia leaves possess LC50 values 259.35, 115.17, 56.84 and 8.73 ppm after 12, 18, 24 and 30 h; the CHCl3 extract possess LC50 values 585.43, 205.86, 112.74, 75.62, 52.84and 47.34 ppm after 12, 18, 24, 30, 36 and 42 h but CH3OH extract possess LC50 values 185.87, 60.70, 30.11 and 15.39 ppm after 12, 18, 24 and 30 h of exposure respectively. The petroleum ether extract of N. Indicum leaves recorded LC50 values 249.82, 146.07, 80.23, 54.21 and 40.19 ppm after 18, 24, 30, 36 and 42 h; the CHCl3 extract gave LC50 values 36.13, 21.72, 19.03, 16.81 and 16.34 ppm after 12, 18, 24, 30 and 36 h but CH3OH extract recorded LC50 values 394.90, 129.69, 81.50, 73.10 and 37.51 ppm after 18, 24, 30, 36 and 42 h of exposure respectively. Similarly, the petroleum ether extract of S. indicum leaves showed LC50 values 24.79, 13.18 and 4.61 ppm after 12, 18 and 24 h; the CHCl3 extract were 50.45, 42.64, 21.20 and 14.93 ppm after 18, 24, 30 and 36 h of exposure and the CH3OH extract showed LC50 values 306.37, 217.18, 149.38, 73.52, 54.45 and 22.91 ppm after 12, 18, 24, 30, 36 and 42 h of exposure respectively. The intensity of efficacy of the extracts could be arranged in the following descending order of S. indicum (petroleum etroleum ether extract) >H. littoralis (CH3OH extract) >M. longifolia (petroleum ether extract) >N. indicum (CHCl3 extract). J. Bio-Sci. 29(2): 139-149, 2021 (December)